Mangrove Blue Carbon in the Face of Deforestation, Climate Change, and Restoration - Friess, D.A.; Krauss, K.W.; Taillardat, P.; Adame, M.F.; Yando, E.S.; Cameron, C.; Sasmito, S.D.; Sillanpää, M. (Wiley, 2020)
Coastal wetlands have disproportionately high carbon densities, known as blue carbon, compared to most terrestrial ecosystems. Mangroves and their blue carbon stocks are at risk globally from land‐use and land‐cover change (LULCC) activities such as aquaculture, alongside biophysical disturbances such as sea‐level rise and cyclones. Global estimates of carbon emissions from mangrove loss have been previously unable to differentiate between the variable impacts of different drivers of loss. This article discusses the impacts that different LULCC activities and biophysical disturbances have on carbon stocks (biomass and soil) and greenhouse gas fluxes (CO2and CH4). The dynamics of carbon stocks and fluxes depends on the type of LULCC; aquaculture often results in biomass and soil carbon removal, and some forms of agriculture can substantially increase methane emissions. Natural disturbances have mixed impacts on mangrove carbon; sea‐level rise will drown some mangroves and their carbon stocks but provide opportunities for new carbon accumulation, while cyclones can have immediate negative impacts on stocks but positive impacts on sequestration during recovery. Mangrove rehabilitation practices can actively restore carbon stocks and reduce greenhouse gas emissions from previous land uses. It is critical to consider the type of LULCC when estimating carbon emissions due to mangrove loss or rehabilitation. Mangrove blue carbon is now high on the international conservation policy agenda, and a better understanding of how carbon stocks and fluxes respond to anthropogenic and biophysical disturbance may provide better incentives for mangrove conservation and sustainable management.